REFORMASI KITAB UNDANG-UNDANG HUKUM PERDATA YANG BERCIRIKHAS INDONESIA DI ERA GLOBALISASI - Krismiyarsi S.H., M.H. (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2013)
Globalization will lead to legal regulations regarding investment, trade, services and other economic areas in the developing countries come near to the developed countries. But there is no guarantee that those legal regulations may provide the same results in all places. This is because of differences in political, economies and cultures systems which differ in each country. Developing countries including Indonesia inevitably finally have to follow such world mainstream. It required the precautionary principle from the Government so that the law of the result of globalization can be applied effectively and not contrary to the Pancasila, Constitution and the laws of life in society. It is not right to set the civil law in one statute book using codification. Therefore, the authors suggest to establish an umbrella legislation (partial codification), which serves as the parent of commercial law and economic law.